Interpersonal Communication in Surah An-Nahl 125: At-Tabari and Fazlur Rahman - Erlangga, Dicky; Khaled Hussein Ahmed, Rania; Rahman , Ainur (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
This study aims to analyze interpersonal communication in Surah An-Nahl verse 125 based on the views of two mufasirs, namely Imam At-Thabari as a representation of classical interpretation and Fazlur Rahman as a representation of modern interpretation. This study aims to identify similarities and differences in the interpretations of the two mufasirs and explore their relevance to Islamic interpersonal communication theory. This research uses a qualitative method with a library research approach. The primary data sources used are Jami' al-Bayan fi Tafsir al-Qur'an by At-Thabari and Major Themes of the Qur'an by Fazlur Rahman. The results showed that Imam At-Thabari emphasized the importance of wisdom as revelation-based wisdom, mau'izhah hasanah as gentle and heartfelt advice, and mujadalah bi allati hiya ahsan as a dialogue based on justice and empathy. On the other hand, Fazlur Rahman offers a modern approach by highlighting contextual and humanist aspects, such as the importance of understanding the culture, psychology, and social conditions of the audience in delivering da'wah messages. This approach is relevant in answering communication challenges in the increasingly complex era of globalization. This research makes an academic contribution by combining classical and modern interpretations in the context of Islamic interpersonal communication theory, as well as offering practical guidance in effective Islamic da'wah that is in accordance with the values of the Islamic religion.